Nanometer glass ceramic, chemical reinforced glass ceramic and preparation method
By preparing and chemically strengthening nano-microcrystalline glass, the shortcomings in optical and mechanical properties of existing microcrystalline glass are solved, high mechanical strength and excellent optical properties are achieved, and glass protective covers suitable for electronic equipment and household appliances, etc. application.
Patent Information
- Application Number
- CN202411170262.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-17
AI Technical Summary
Existing microcrystalline glass products are difficult to meet the wide application needs in terms of optical performance and mechanical strength performance, especially in practical applications in consumer and commercial electronic equipment, stoves, cooking utensils and other fields.
By preparing a nanocrystalline glass, its components include greater than or equal to 40% and less than or equal to 60% SiO2, greater than or equal to 15% and less than or equal to 28% Al2O3, greater than or equal to 1% in molar percentage And less than or equal to 5% Li2O, greater than or equal to 12% and less than or equal to 20% Na2O, and control the main crystal phase to K0.1Na3Al3.12Si4.88O16 and the grain size is less than 20nm, combined with optional components such as CaO , MgO, SnO2, Sb2O3, ZrO2, etc., heat treatment is carried out to form a specific crystal phase and grain distribution, and performance is further improved through chemical strengthening treatment.
The excellent optical and high mechanical strength properties of nano-crystalline glass have been achieved, with the surface compressive stress reaching 1340~1400Mpa, the stress layer depth is 30~37μm, the four-point bending strength test value is 1300~1380Mpa, and the thickness of 0.6mm is relative to 64g The impact resistance height of the steel ball is greater than or equal to 2000 mm, and maintains a visible light transmittance of more than 91% at a thickness of 0.5 mm.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the field of material technology, and in particular to the field of glass technology. Specifically, the present application discloses a nano-ceramic glass, a chemically strengthened glass-ceramic glass, and a preparation method thereof. Background Art
[0002] Glass-ceramic products such as glass cover plates, glass back plates, housings, and the like are widely used in consumer and commercial electronic devices, such as smart phones, tablet computers, etc. Of course, in the known material classification, glass-ceramic products are also widely used in various other applications, such as stoves, cooking utensils, tableware, optical components, etc. At present, many application fields require glass-ceramic to provide excellent optical properties and high mechanical strength properties, but the glass-ceramic provided in the relevant technology is still difficult to meet the actual application requirements.
[0003] It is worth noting that the techniques described in this section are not necessarily techniques that have been previously conceived or employed. Unless otherwise indicated, it should not be assumed that any technique described in this section is considered to be prior art simply because it is included in this section. Similarly, unless otherwise indicated, the issues mentioned in this section should not be considered to have been recognized in any prior art. Summary of the invention
[0004] The present application provides a nano-ceramic glass, a chemically strengthened glass-ceramic glass and a preparation method, aiming to solve at least one of the problems in the related art to a certain extent.
[0005] The first aspect of the present application provides a nano-ceramic glass, wherein the components thereof are, in molar percentage, greater than or equal to 40% and less than or equal to 60% of SiO2, greater than or equal to 15% and less than or equal to 28% of Al2O3, greater than or equal to 1% and less than or equal to 5% of Li2O, greater than or equal to 12% and less than or equal to 20% of Na2O, and greater than 0 and less than or equal to 3% of K2O; the main crystalline phase of the nano-ceramic glass includes K 0.1 Na3Al 3.12 Si 4.88 O 16 , and the grain size of the nano-ceramic glass is less than 20nm.
[0006] Optionally, the components of the nano-glass-ceramics, expressed in molar percentage, further include: greater than or equal to 0.5% and less than or equal to 7% of CaO, and greater than or equal to 1% and less than or equal to 8% of MgO.
[0007] Optionally, the main crystalline phase of the nano-ceramic glass also includes K 0.1 Na 3.3 Ca 0.3 Al4(SiO4)4.
[0008] Optionally, the components of the nano-glass-ceramics, expressed in molar percentage, further include: a clarifier; the clarifier includes: greater than or equal to 0.01% and less than or equal to 0.2% SnO2, greater than or equal to 0.01% and less than or equal to 0.2% Sb2O3.
[0009] Optionally, the components of the nano-glass-ceramics, expressed in molar percentage, further include: a nucleating agent; the nucleating agent includes: greater than or equal to 0.3% and less than or equal to 2% of ZrO2.
[0010] Optionally, the components of the nano-glass-ceramics, measured in molar percentage, also include: greater than or equal to 0 and less than or equal to 0.3% ZnO, greater than or equal to 0 and less than or equal to 1.5% B2O3, greater than or equal to 0 and less than or equal to 0.15% La2O3, and greater than or equal to 0 and less than or equal to 0.5% Y2O3.
[0011] Optionally, the nano-ceramic glass meets at least one of the following performance indicators: hardness of 510*10 7 ~537*10 7 Pa, elastic modulus is 82~89GPa, shear modulus is 30~33.76GPa, and Poisson's ratio is 0.24~0.36.
[0012] Optionally, the secondary crystalline phase of the nano-glass-ceramics includes cristobalite.
[0013] Optionally, the grain size distribution of the nano-ceramic glass satisfies the following conditions: the number of grains with a size less than 10 nm accounts for greater than or equal to 30%, the number of grains with a size of 10 nm to 15 nm accounts for greater than or equal to 60%, and the number of grains with a size of 15 nm to 20 nm accounts for less than 5%.
[0014] The second aspect of the present application provides a chemically strengthened glass-ceramics, which is obtained by chemically strengthening the nano-glass-ceramics described in the first aspect of the present application.
[0015] Optionally, the chemically strengthened microcrystalline glass meets at least one of the following performance indicators: surface compressive stress of 1340-1400Mpa, stress layer depth of 30-37μm, four-point bending strength test value of 1300-1380Mpa, impact resistance height relative to 64g steel ball at 0.6mm thickness is greater than or equal to 2000mm, and transmittance relative to 380nm visible light at 0.5mm thickness is greater than or equal to 91%.
[0016] The third aspect of the present application provides a method for preparing nano-microcrystalline glass, comprising: preparing raw materials with corresponding formula proportions according to the components of the nano-microcrystalline glass, wherein the components of the nano-microcrystalline glass, in molar percentage, include: greater than or equal to 40% and less than or equal to 60% SiO2, greater than or equal to 15% and less than or equal to 28% Al2O3, greater than or equal to 1% and less than or equal to 5% Li2O, greater than or equal to 12% and less than or equal to 20% Na2O, greater than 0 and less than or equal to 3% K2O; after uniformly mixing the raw materials, smelting them at a preset melting temperature for a preset time to obtain the precursor glass; heat-treating the precursor glass to obtain the nano-microcrystalline glass, wherein the main crystalline phase of the nano-microcrystalline glass includes K 0.1 Na3Al 3.12 Si 4.88 O 16 , and the grain size of the nano-ceramic glass is less than 20nm.
[0017] Optionally, the step of heat treating the precursor glass to obtain nano-microcrystalline glass includes: heating the precursor glass to (Tg+30)°C at a heating rate of 5°C / h, and keeping it warm for 20 hours, and then cooling it to (Tg-100)°C at a cooling rate of 1.5-2°C / h to obtain nano-microcrystalline glass; wherein Tg is the glass transition temperature.
[0018] As can be seen from the above, according to the nano-ceramic glass, chemically strengthened glass-ceramic and preparation method provided by the present application, the components of the nano-ceramic glass, in molar percentage, include: greater than or equal to 40% and less than or equal to 60% SiO2, greater than or equal to 15% and less than or equal to 28% Al2O3, greater than or equal to 1% and less than or equal to 5% Li2O, greater than or equal to 12% and less than or equal to 20% Na2O, greater than 0 and less than or equal to 3% K2O; the main crystalline phase of the nano-ceramic glass includes K 0.1 Na3Al 3.12 Si 4.88 O 16 , and the size of the nano-ceramic glass grains is less than 20nm. The present application controls the oxide content in the glass-ceramic within a specific ratio, and makes the main crystal phase and grain size of the glass-ceramic meet specific requirements, which can ensure that the strengthened glass-ceramic has excellent optical properties and high mechanical strength.
[0019] It should be understood that the content described in this section is not intended to identify the key or important features of the present application, nor is it intended to limit the scope of the present application. Other features of the present application will become easily understood through the following description. DETAILED DESCRIPTION
[0021] In the description of the embodiments of the present application, the term "plurality" means two or more than two, unless otherwise clearly and specifically defined; the term "comprising" indicates the presence of the described features, wholes, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections; the term "and / or" describes the association relationship of the associated objects, indicating that three relationships may exist. For example, A and / or B may include the three situations of A existing alone, A and B existing at the same time, and B existing alone. The character " / " generally indicates that the associated objects before and after are in an "or" relationship; the term "approximately" means that the content, size, parameter, etc. are not and do not need to be precise. If necessary, they can be approximate or higher or lower. Generally speaking, regardless of whether there is an explicit description, the content, size, parameter, etc. should be "approximately" or "approximately"; the terms "preferably" and "optional" are not used to limit the scope of the present application, nor do they mean that certain technical features are critical or indispensable to the implementation methods of the present application, but should be understood as only indicating specific aspects of the embodiments of the present application.
[0022] In addition, when used to indicate components and contents, the terms "does not contain", "does not include", "is not introduced", and "0" mean that the relevant components or substances are not actively and intentionally added to the glass, but may be passively and unexpectedly introduced into the glass as indefinite (small or trace) impurities.
[0023] Unless otherwise specified in specific circumstances, the numerical ranges recorded in the examples of the present application are intended to include the endpoints of the numerical range and all integers and fractions within the range. When describing a certain amount, solubility or other parameter in the form of a preferred range or a preferred value, it should be understood that it is equivalent to revealing any range by combining any preferred range with a preferred range, a preferred value with a preferred value, or a preferred range with a preferred value, without considering whether this combination is specifically explained in the examples.
[0024] Unless otherwise specified in specific circumstances, the component contents described in the examples of the present application are expressed in molar percentage (mol%).
[0025] In order to at least to some extent solve the problem of relatively limited optical properties and mechanical strength properties of microcrystalline glass products provided in the relevant technology, an embodiment of the present application provides a nano-microcrystalline glass, whose components, measured in molar percentage (mol%), include: greater than or equal to 40% and less than or equal to 60% SiO2, greater than or equal to 15% and less than or equal to 28% Al2O3, greater than or equal to 1% and less than or equal to 5% Li2O, greater than or equal to 12% and less than or equal to 20% Na2O, and greater than 0 and less than or equal to 3% K2O.
[0026] SiO2 is the basic component of the glass composition provided in this application, and is a network structure former of glass and glass-ceramics, which can form a specific crystalline phase after crystallization. It should be noted that if the content of SiO2 is low, then the crystals formed in the nano-ceramic glass will become less and the crystals will become coarser, which will affect the light transmittance, drop ball test height and other properties of the glass-ceramic products (i.e., nano-ceramic glass or chemically strengthened glass-ceramic). Therefore, the lower limit of the SiO2 content is preferably 40%; in addition, if the SiO2 content is higher than a certain level, the glass melting temperature will be high, the material will be difficult to form, and it will not be easy to shape, which will affect the consistency of the glass. Therefore, the upper limit of the SiO2 content in this embodiment is preferably 60%. In some embodiments, the glass composition may include about 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60% SiO2. Preferably, the content of SiO2 is 46-58%.
[0027] Al2O3 can be a component that forms a glass network structure, or it can be a cationic network exosome that balances charge. In the present application, all Al2O3 enters the glass network structure, improves the chemical stability of the glass, improves the mechanical properties of the glass, and increases the depth of the ion exchange layer and the surface stress of the nano-ceramic glass. On the one hand, if its content is lower than a certain level, it will lead to poor results. Therefore, the lower limit of the molar percentage content of Al2O3 is 15%; on the other hand, if the content of Al2O3 is higher than a certain level, the melting and devitrification resistance of the glass will be reduced, and the crystals will easily increase during crystallization, reducing the strength of the microcrystalline glass products. Therefore, the upper limit of the Al2O3 content in this embodiment is 28%. In some embodiments, the glass composition may contain about 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28% Al2O3. Preferably, the content of Al2O3 is 19-25%.
[0028] Li2O is a necessary component for ion exchange, and its content is an important factor affecting the stress of microcrystalline glass. Li2O can also provide free oxygen to change the viscosity of glass. However, if its content is lower than a certain level, it is easy to precipitate unexpected crystalline phases, making the glass devitrified, difficult to clarify, and difficult to shape. Therefore, the lower limit of the Li2O content in this embodiment is 1%. On the other hand, if too much Li2O is contained, it is easy to reduce the chemical stability of the glass and increase the product cost. Therefore, the upper limit of the Li2O content is preferably 5%. In some embodiments, the glass composition may contain about 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% Li2O. Preferably, the content of Li2O is 1-3%.
[0029] It is worth mentioning that the glass composition of the present application is further configured with two other alkali metal oxides, K2O and Na2O, in addition to the alkali metal oxide Li2O. It should be noted that, on the one hand, K2O and Na2O are the components that form the expected crystalline phase K 0.1 Na3Al 3.12 Si 4.88 O 16 on the other hand, the various alkali metal oxides of this embodiment can exert a mixed alkali effect when the glass is chemically strengthened, and can restrict the migration of alkali metal ions during the ion diffusion process, which helps to improve the chemical stability of the glass. In addition, the various alkali metal oxides interact with each other, which helps to improve the low-temperature melting and formability of the glass, and have a certain effect on reducing the softening point of the glass composition and the mold temperature during molding, thereby reducing the difficulty of chemical strengthening of the microcrystalline glass during chemical strengthening treatment and improving the chemical strengthening efficiency.
[0030] It should be noted that, based on comprehensive considerations of the optical properties, mechanical strength, chemical stability and chemical strengthening efficiency of the glass, in this embodiment, on the basis of the glass composition containing 1-5% Li2O, the content of Na2O is set to be greater than or equal to 12% and less than or equal to 20%, and the content of K2O is set to be greater than 0 and less than or equal to 3%; the molar percentage of Na2O can be exemplarily 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, and the molar percentage of K2O can be exemplarily 0.1%, 0.5%, 1, 1.5%, 2%, 2.5%, 3%. In this embodiment, preferably, the content of Na2O is greater than or equal to 14% and less than or equal to 18%, and the content of K2O is greater than 0 and less than or equal to 2%.
[0031] In an optional implementation manner of this embodiment, the components of the nano-glass-ceramics, measured in molar percentage, further include: greater than or equal to 0.5% and less than or equal to 7% of CaO, greater than or equal to 1% and less than or equal to 8% of MgO.
[0032] CaO helps to reduce the viscosity of glass and improve its meltability and formability. In order to avoid the increase of glass density and thermal expansion coefficient due to the introduction of CaO, the upper limit of CaO contained in the glass composition of this embodiment is 7%. In some embodiments, the glass composition may contain about 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7% CaO. Preferably, the content of CaO is 1-6%.
[0033] MgO helps to reduce the viscosity of glass, inhibit the tendency of crystallization during glass forming, and improve low-temperature melting. MgO is an optional component, but if the MgO content is too high, it may cause a decrease in devitrification resistance, and undesirable crystals will be obtained after crystallization, resulting in a decrease in the performance of microcrystalline glass and microcrystalline glass products. Therefore, the upper limit of the MgO molar percentage content is 8%. In some embodiments, the glass composition may include about 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8% MgO. Preferably, the content of MgO is 3 to 5.5%.
[0034] In an optional implementation manner of this embodiment, the components of the nano-glass-ceramics, in molar percentage, also include: a clarifier; the clarifier includes: greater than or equal to 0.01% and less than or equal to 0.2% SnO2, greater than or equal to 0.01% and less than or equal to 0.2% Sb2O3.
[0035] The clarifier can discharge bubbles during the glass melting process. When the content of SnO2 is too high, it is easy to cause the color of the glass to change. Therefore, the upper limit of SnO2 contained in the glass composition of this embodiment is 0.01%. In some embodiments, the glass composition may contain about 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2% SnO2. Preferably, the content of SnO2 is 0.05-0.1%. In addition, the fining agent also includes about 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2% Sb2O3. Preferably, the content of Sb2O3 is 0.04-0.2%.
[0036] More preferably, the total content of SnO2 and Sb2O3 is 0.1-0.2%. In some embodiments, the total content of SnO2 and Sb2O3 in the glass composition is about 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%. This can achieve a composite clarification effect, so that the glass bubbles are removed more thoroughly.
[0037] In an optional implementation manner of this embodiment, the components of the nano-glass-ceramics, measured in molar percentage, further include: a nucleating agent; the nucleating agent includes: greater than or equal to 0.3% and less than or equal to 2% ZrO2.
[0038] Because the cation of ZrO2 has the characteristics of high charge and strong field, it has a large aggregation effect on the glass network structure, so it is often used as a nucleating agent, and it also helps to improve the chemical stability of the glass. The lower limit of the ZrO2 content in this application is 0.3%, but if too much ZrO2 is contained, the devitrification resistance of the glass is easily reduced, and the difficulty of controlling the glass crystallization process increases. Therefore, the upper limit of the ZrO2 content is 2%. In some embodiments, the glass composition may contain about 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% ZrO2. Preferably, the content of ZrO2 is 0.5-1%. Since TiO2 may reduce the transmittance of glass to visible light in the wavelength range of 300 to 400 nm, it is further preferred that the nucleating agent of this embodiment does not include TiO2.
[0039] In order to ensure that the mechanical properties such as hardness, elastic modulus, shear modulus and low-temperature thermal properties of the microcrystalline glass products of the present application are within the expected range, in an optional implementation manner of this embodiment, the components of the nano-microcrystalline glass, expressed in molar percentage, also include: greater than or equal to 0 and less than or equal to 0.3% ZnO, greater than or equal to 0 and less than or equal to 1.5% B2O3, greater than or equal to 0 and less than or equal to 0.15% La2O3, greater than or equal to 0 and less than or equal to 0.5% Y2O3.
[0040] ZnO can improve the melting properties of glass, improve the chemical stability of glass, and refine grains during crystallization. Controlling the upper limit of the ZnO molar percentage content to below 0.3% can inhibit the reduction of devitrification. In some embodiments, the glass composition may include approximately 0, 0.1%, 0.15%, 0.2%, 0.25%, and 0.35% ZnO.
[0041] B2O3 can reduce the viscosity of the glass and improve the melting difficulty caused by ZrO2. When its content is too high, the devitrification resistance of the glass is reduced. Therefore, in order to improve the formability of the glass and obtain nano-microcrystalline glass with desired performance, the molar percentage content of B2O3 is preferably controlled below 1.5%. In some embodiments, the glass composition may contain approximately 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, and 1.5% B2O3.
[0042] La2O3 and Y2O3 can be used to fill the gaps in the glass network to make the glass structure denser. In order to avoid excessive density and refractive index of the glass and a large decrease in the expansion coefficient, in some embodiments, the glass composition may contain approximately 0, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, and 0.15% La2O3; in other embodiments, the glass composition may contain approximately 0, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, and 0.5% Y2O3.
[0043] In an optional implementation manner of this embodiment, the components of the nano-glass-ceramics, measured in molar percentage, also include: Bi2O3: 0-0.68%.
[0044] In the related art, glass raw materials are melted to obtain precursor microcrystalline glass, and the glass melting temperature in the related art is usually high (for example, around 1600°C), which makes glass melting difficult. Based on this, this embodiment introduces Bi2O3 components into the glass composition. Bi2O3 can reduce the viscosity of the glass. Since the glass melting temperature is the temperature when log(P)=2, P represents the viscosity of the glass, and thus reducing the viscosity of the glass can reduce the temperature required for glass melting, thereby reducing the difficulty of glass melting. It is worth mentioning that too high a content of Bi2O3 will cause glass coloring, so the upper limit of the content of Bi2O3 is set to 0.68%. In some embodiments, the glass composition may contain about 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, and 0.68% Bi2O3.
[0045] It is worth mentioning that the main crystalline phase of nano-glass-ceramics includes K 0.1 Na3Al 3.12 Si 4.88 O 16 In an optional embodiment, the main crystalline phase of the nano-ceramic glass also includes K 0.1 Na 3.3 Ca 0.3 Al4(SiO4)4, in an optional embodiment, the secondary crystalline phase of the nano-ceramic glass comprises cristobalite. It should be understood that the main crystalline phase is also called the main crystalline phase, which refers to a crystalline phase with a higher content than other crystalline phases present in the nano-ceramic glass.
[0046] In addition, the size of the crystal grains of the nano-ceramic glass is less than 20nm. Optionally, the crystal grain size distribution of the nano-ceramic glass satisfies the following conditions: the number of crystal grains less than 10nm accounts for greater than or equal to 30%, the number of crystal grains with a size of 10nm to 15nm accounts for greater than or equal to 60%, and the number of crystal grains with a size of 15nm to 20nm accounts for less than 5%. It is worth mentioning that the size of the crystal grains in this embodiment can be understood as the crystal grain diameter.
[0047] In the grain size distribution of the nano-ceramic glass of this embodiment, the sum of the number of grains of different sizes is 100%. In order to ensure the optical performance and mechanical strength performance, this embodiment improves the optical performance and mechanical strength performance by reasonably controlling the grain size distribution. Generally speaking, when there are more small-sized grains, the optical performance is good but the mechanical strength performance is not enough, and when there are more large-sized grains, the optical performance will be reduced. Therefore, this embodiment controls the grain size distribution within the design range to achieve the desired balance between optical performance and mechanical strength performance.
[0048] The precursor glass used to prepare the nano-ceramic glass of this embodiment meets at least one of the following performance indicators: glass transition temperature Tg is 662-704°C, sag temperature Ts is 742-782°C, thermal expansion coefficient α is 82-89.92 at 100-300°C, hardness HK is 493*10 7 ~520*10 7 Pa, elastic modulus is 78-86 GPa, shear modulus is 30-34.8 GPa, Poisson's ratio is 0.17-0.35, refractive index nd is 1.53030-1.53920, density ρ is 2.5951-2.6044 g / cm 3 , the transmittance with respect to 380nm visible light at a thickness of 0.6mm is greater than or equal to 90.9%.
[0049] Based on the aforementioned glass-ceramics formula provided in the embodiment of the present application and the aforementioned main crystalline phase setting of the embodiment of the present application, the nano-glass-ceramics can meet at least one of the following performance indicators: hardness of 510*10 7 ~537*10 7 Pa, elastic modulus is 82-89 GPa, shear modulus is 30-33.76 GPa, and Poisson's ratio is 0.24-0.36. It can be seen that the embodiments of the present application effectively improve the mechanical strength performance of nano-ceramic glass.
[0050] Next, an embodiment of the present application further provides a chemically strengthened glass-ceramic, which is obtained by chemically strengthening the nano-glass-ceramic provided in any of the above embodiments (also known as ion exchange treatment). It is worth mentioning that the chemically strengthened glass-ceramic includes a compressive stress layer extending from the surface of the glass-ceramic to the depth of the ion exchange layer.
[0051] It is worth mentioning that chemical strengthening treatment refers to placing nano-glass-ceramics in a salt bath for ion exchange treatment, so that the glass-ceramics forms a compressive stress layer and a tensile stress layer. The chemical strengthening salt bath includes a sodium ion salt bath or a potassium ion salt bath. The components of the sodium ion salt bath include one or more of sodium nitrate, sodium carbonate, and sodium sulfate. The components of the potassium ion salt bath include one or more of potassium nitrate, potassium carbonate, and potassium sulfate. The number of ion exchange treatments is at least one. When the number of ion exchange treatments is multiple, the salt baths used for multiple ion exchange treatments may be different.
[0052] It should be noted that the chemically strengthened microcrystalline glass of this embodiment meets at least one of the following performance indicators: surface compressive stress CS is 1340~1400Mpa, stress layer depth DOL is 30~37μm, four-point bending strength test value is 1300~1380Mpa, impact resistance height relative to 64g steel ball at 0.6mm thickness is greater than or equal to 2000mm, and transmittance relative to 380nm visible light at 0.6mm thickness is greater than or equal to 91%.
[0053] Accordingly, an embodiment of the present application further provides a method for preparing nano-glass-ceramics, which specifically includes the following process:
[0054] Step A, preparing raw materials in corresponding formula proportions according to the components of nano-glass-ceramics;
[0055] Step B, after the raw materials are evenly mixed, they are melted at a preset melting temperature for a preset time to obtain a precursor glass;
[0056] Step C: heat-treating the precursor glass to obtain nano-ceramic glass.
[0057] On the one hand, the components of the nano-ceramic glass, measured in molar percentage, include: greater than or equal to 40% and less than or equal to 60% SiO2, greater than or equal to 15% and less than or equal to 28% Al2O3, greater than or equal to 1% and less than or equal to 5% Li2O, greater than or equal to 12% and less than or equal to 20% Na2O, and greater than 0 and less than or equal to 3% K2O.
[0058] On the other hand, the main crystalline phase of the nano-ceramic glass includes K 0.1 Na3Al 3.12 Si 4.88O 16 Furthermore, the main crystalline phase of the nano-ceramic glass also includes K 0.1 Na 3.3 Ca 0.3 Al4(SiO4)4, the secondary crystalline phase includes cristobalite. And the size of the crystal grains of the nano-ceramic glass is less than 20nm, and further, the grain size distribution satisfies the following conditions: the number of crystal grains with a size less than 10nm accounts for greater than or equal to 30%, the number of crystal grains with a size of 10nm to 15nm accounts for greater than or equal to 60%, and the number of crystal grains with a size of 15nm to 20nm accounts for less than 5%.
[0059] It is worth mentioning that in order to achieve the formation of only the expected type of crystalline phase in the nano-microcrystalline glass, achieve the expected grain size distribution and the expected optical / mechanical properties, in the process of heat treatment of the precursor glass in this embodiment, preferably, the precursor glass is heated to (Tg+30)°C at a heating rate of 5°C / h, and kept warm for 20 hours, and then cooled to (Tg-100)°C at a cooling rate of 1.5-2°C / h to obtain nano-microcrystalline glass; wherein Tg is the glass transition temperature.
[0060] Generally speaking, the glass transition temperature refers to the highest temperature at which glass becomes brittle, also known as the glass brittle temperature. At this temperature, the internal stress of the glass caused by uneven cooling can be eliminated. In practical applications, this temperature can be obtained through the DSC curve of the precursor glass.
[0061] In order to illustrate the technical effects of the nano-microcrystalline glass and chemically strengthened microcrystalline glass of this embodiment, the present application conducted tests on precursor glasses and microcrystalline glasses of different components and contents to determine the corresponding properties, and the test results are shown in Table 1. For details, please see the data shown in Examples 1 to 8 of Table 1.
[0062] Table 1 Examples 1 to 8
[0063]
[0064]
[0065] According to the performance indicators related to mechanical strength shown in the embodiment of the present application in Table 1 above, the hardness of the nano-ceramic glass provided in the embodiment of the present application can reach 50*10 7Pa or more, the elastic modulus can reach more than 80Gpa, the shear modulus can reach more than 30Gpa, and the surface compressive stress of the chemically strengthened microcrystalline glass can reach more than 1340Mpa, the stress layer depth can reach more than 30μm, the four-point bending strength test value 4PB can reach more than 1350Mpa, and the impact resistance height relative to a 64g steel ball at a thickness of 0.6mm can reach more than 2000mm. It can be seen that the microcrystalline glass products containing the formula composition provided in the embodiments of the present application can achieve relatively excellent mechanical strength performance.
[0066] In addition, according to the performance indicators related to optical properties shown in the embodiments in Table 1 above of the present application, it can be seen that the transmittance of the nano-crystalline glass and chemically strengthened glass provided in the embodiments of the present application relative to 380nm visible light at a thickness of 0.6mm can reach more than 91%. Therefore, it can be seen that the nano-crystalline glass products containing the formula composition provided in the embodiments of the present application can achieve relatively excellent optical properties.
[0067] Based on the above scheme of the present application, the nano-ceramic glass introduces the following components, in molar percentage: greater than or equal to 40% and less than or equal to 60% SiO2, greater than or equal to 15% and less than or equal to 28% Al2O3, greater than or equal to 1% and less than or equal to 5% Li2O, greater than or equal to 12% and less than or equal to 20% Na2O, greater than 0 and less than or equal to 3% K2O; the main crystalline phase of the nano-ceramic glass includes K 0.1 Na3Al 3.12 Si 4.88 O 16 , and the size of the crystal grains of the nano-ceramic glass is less than 20nm. The present application controls the oxide content in the glass-ceramic to a specific ratio, and makes the main crystal phase and the grain size of the glass-ceramic meet specific requirements. After chemical strengthening, the transmittance relative to 380nm visible light at a thickness of 0.6mm can be greater than 91%, and the impact height of the 64g drop ball test can reach more than 2000mm, thereby ensuring that the strengthened glass-ceramic has excellent optical properties and high mechanical strength properties.
[0068] It is also worth mentioning that, due to the above-mentioned performance advantages of the nano-glass-ceramics and chemically strengthened glass-ceramics provided in the embodiments of the present application, they can be widely used in the manufacture of glass protective cover plates for electronic devices, glass components or windows for household appliances, etc.
[0069] Finally, it should be noted that in the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0070] The above is a description of the nano-microcrystalline glass, chemically strengthened microcrystalline glass and preparation method provided in this application. For those skilled in the art, based on the ideas of the embodiments of this application, equivalent substitutions made in the specific implementation methods and application scopes should all be included in the scope of the claims of this application. In summary, the content of this specification should not be understood as a limitation on the scheme of this application.
Claims
1. A nano-ceramic glass, characterized in that: The components thereof include, by mole percentage, greater than or equal to 40% and less than or equal to 60% of SiO2, greater than or equal to 15% and less than or equal to 28% of Al2O3, greater than or equal to 1% and less than or equal to 5% of Li2O, greater than or equal to 12% and less than or equal to 20% of Na2O, and greater than 0 and less than or equal to 3% of K2O; the main crystalline phase of the nano-ceramic glass includes K 0.1 Na3Al 3.12 Si 4.88 O 16 , and the grain size of the nano-ceramic glass is less than 20nm.
2. The nano-ceramic glass according to claim 1, characterized in that: Its components, measured in molar percentage, include: greater than or equal to 46% and less than or equal to 58% of SiO2, greater than or equal to 19% and less than or equal to 25% of Al2O3, greater than or equal to 1% and less than or equal to 3% of Li2O, greater than or equal to 14% and less than or equal to 18% of Na2O, and greater than 0 and less than or equal to 2% of K2O.
3. The nano-ceramic glass according to claim 1, characterized in that: The components thereof further include, in molar percentage, greater than or equal to 0.5% and less than or equal to 7% of CaO, and greater than or equal to 1% and less than or equal to 8% of MgO.
4. The nano-ceramic glass according to claim 3, characterized in that: The components thereof further include, in molar percentage, greater than or equal to 1% and less than or equal to 6% of CaO, and greater than or equal to 3% and less than or equal to 5.5% of MgO.
5. The nano-ceramic glass according to claim 3, characterized in that: The main crystalline phase also includes K 0.1 Na 3.3 Ca 0.3 Al4(SiO4)4.
6. The nano-ceramic glass according to claim 1, characterized in that: Its components, measured in molar percentage, also include: a clarifier; the clarifier includes: greater than or equal to 0.01% and less than or equal to 0.2% of SnO2, greater than or equal to 0.01% and less than or equal to 0.2% of Sb2O3.
7. The nano-ceramic glass according to claim 6, characterized in that: The total content of SnO2 and Sb2O3 is 0.1-0.2%.
8. The nano-ceramic glass according to claim 6, characterized in that: The components thereof, measured in molar percentage, further include: a nucleating agent; the nucleating agent includes: ZrO2 in an amount greater than or equal to 0.3% and less than or equal to 2%.
9. The nano-ceramic glass according to claim 8, characterized in that: Its components, measured in molar percentage, also include: greater than or equal to 0 and less than or equal to 0.3% of ZnO, greater than or equal to 0 and less than or equal to 1.5% of B2O3, greater than or equal to 0 and less than or equal to 0.15% of La2O3, and greater than or equal to 0 and less than or equal to 0.5% of Y2O3.
10. The nano-ceramic glass according to claim 1, characterized in that: Meet at least one of the following performance indicators: hardness is 510*10 7 ~537*10 7 Pa, elastic modulus is 82~89GPa, shear modulus is 30~33.76GPa, and Poisson's ratio is 0.24~0.
36.
11. The nano-ceramic glass according to claim 1, characterized in that: The secondary crystalline phase of the nano-ceramic glass includes cristobalite.
12. The nano-ceramic glass according to any one of claims 1 to 11, characterized in that: The grain size distribution of the nano-ceramic glass meets the following conditions: the number of grains with a size less than 10nm accounts for greater than or equal to 30%, the number of grains with a size of 10nm-15nm accounts for greater than or equal to 60%, and the number of grains with a size of 15nm-20nm accounts for less than 5%.
13. A chemically strengthened glass-ceramic, characterized in that: The chemically strengthened glass-ceramics is obtained by subjecting the nano-ceramics according to any one of claims 1 to 12 to chemical strengthening treatment.
14. The chemically strengthened glass-ceramics according to claim 13, characterized in that: Meet at least one of the following performance indicators: surface compressive stress is 1340-1400Mpa, stress layer depth is 30-37μm, four-point bending strength test value is 1300-1380Mpa, impact resistance height relative to 64g steel ball at 0.6mm thickness is greater than or equal to 2000mm, and transmittance relative to 380nm visible light at 0.6mm thickness is greater than or equal to 91%.
15. A method for preparing nano-glass-ceramics, characterized in that: include: Prepare raw materials with corresponding formula proportions according to the components of nano-ceramic glass; wherein the components of the nano-ceramic glass, in terms of molar percentage, include: greater than or equal to 40% and less than or equal to 60% SiO2, greater than or equal to 15% and less than or equal to 28% Al2O3, greater than or equal to 1% and less than or equal to 5% Li2O, greater than or equal to 12% and less than or equal to 20% Na2O, and greater than 0 and less than or equal to 3% K2O; After the raw materials are uniformly mixed, they are melted at a preset melting temperature for a preset time to obtain a precursor glass; The precursor glass is heat treated to obtain the nano-ceramic glass; wherein the main crystalline phase of the nano-ceramic glass includes K 0.1 Na3Al 3.12 Si 4.88 O 16 , and the grain size of the nano-ceramic glass is less than 20nm.
16. The method for preparing nano-glass-ceramics according to claim 15, characterized in that: The step of heat treating the precursor glass to obtain nano-ceramic glass comprises: The precursor glass is heated to (Tg+30)°C at a heating rate of 5°C / h and kept warm for 20 hours, and then cooled to (Tg-100)°C at a cooling rate of 1.5-2°C / h to obtain nano-ceramic glass; wherein Tg is the glass transition temperature.
Citation Information
Patent Citations
Crystallized glass and crystallized glass substrate
CN106242299A
Transparent glass-ceramic articles, glass-ceramic precursor glasses and methods for forming the same
CN106660860A
Glass ceramic and preparation method thereof and terminal
CN110217996A
Microcrystalline glass, chemically strengthened microcrystalline glass, preparation methods of microcrystalline glass and chemically strengthened microcrystalline glass, and electronic equipment
CN112919812A
Glass ceramic and preparation method thereof, glass protection layer, glass cover plate and electronic device
CN113831021A
Cited By
High-modulus glass, protective film, cover plate layer, display module, and electronic device
WO2026144573A1
